Odpowiedzi

Najlepsza Odpowiedź!
2010-01-20T19:21:02+01:00
A) (a+b)-(2a-b)-(a-2b)= a+b-2a+b-a+2b=-2a+4b

b)(3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x=x-y

c) -(kx+ny)-(3kx+2ny)+(5kx-3ny)= -kx-ny-3kx-2ny+5kx-3ny=kx-6ny
1 5 1
2010-01-20T19:22:42+01:00
A) (a+b)-(2a+b)-(a-2)= a+b-2a-b-a+2= -2a+2
b)(3x-y+1)-(x+y)+(y-x)= 3x-y+1-x-y+y-x=x+y+1
c) -(kx+ny)-(3kx+2ny)+(5kx-3ny)= -kx-ny-3kx-2ny+5kx-3ny=kx-6ny
2010-01-20T19:22:44+01:00
Od razu rozwiązuje
a)a+b-2a+b-a+2b=-2a+4b
b)3x-y+1-x-y+y-x=x-y+1
c)-kx+ny-3kx-2ny+5kx-3ny=kx-4ny